Transdisciplinary Research in Energetics and Cancer early career investigator training program: first year results. Issue 2 (17th February 2020) - Irwin, Melinda L; Lowry, Diana; Neuhouser, Marian L; Ligibel, Jennifer; Schmitz, Kathryn; Patterson, Ruth E; Colditz, Graham; Li, Fangyong; Nebeling, Linda
Abstract: Energy imbalance increases cancer burden by increasing cancer risk and mortality. Training early career investigators on conducting impactful energy balance and cancer research is needed. We developed a Transdisciplinary Research in Energetics and Cancer (TREC) Training Program for early career investigators. This analysis examined program satisfaction, knowledge gained, publications, and awards among Year 1 participants (i.e., fellows). The program consists of an in-person course, followed by 1 year of mentorship. Faculty and fellows completed precourse and postcourse surveys. Following the mentorship period, we surveyed fellows for TREC-related research productivity, including publications and grant funding attributed to the program. Twenty fellows were accepted into the program: 3 basic, 7 clinical, and 10 population scientists. Sixteen fellows were junior faculty and four were postdoctoral fellows. The course included 50 lectures, small group sessions, and faculty–fellow sessions. 96.7% of attendees rated the course in the highest categories of "good/very good." Knowledge significantly improved in 37 of 39 research competencies (94.8%). In the 18 months following the course, fellows published 25 manuscripts, with 3 published in journals with impact factor ≥10. Nineteen grants were funded to TREC fellows (i.e., 7 National Institutes of Health awards, 2 American Cancer Society [ACS] awards, and 10 foundation/pilot awards), and 7 fellows received career promotions. The program's impact will be defined by the degree to which TREC fellows produce discoveries that could improve the health of populations at risk for and/or surviving cancer. Upon the conclusion of our fifth year in 2021, we will publicly disseminate the program material.